Pengaruh Persepsi Risiko, Keamanan Data, dan Transparansi terhadap Kepercayaan Nasabah Generasi Z pada Layanan Digital Bank Syariah Di Kabupaten Sumenep - Utami , Kristiani (JES (Jurnal Ekonomi Syariah), 2026)
This study aims to examine and analyze the influence of risk perception, data security, and transparency on Generation Z customers' trust in Islamic banking digital services. Generation Z, as a digital native group, has unique characteristics in perceiving digital risks and security, but the adoption of Islamic mobile banking services still shows gaps compared to conventional banks. Issues of data leaks, cyber attacks, and suboptimal information transparency are the background to the importance of this study. The approach used is quantitative with a causal associative research type. The study population is all Generation Z customers using Islamic banking digital services in Sumenep Regency, whose exact number is unknown. The sample was determined using the Lemeshow formula and obtained 100 respondents with a purposive sampling technique based on the criteria of 15-30 years of age, active customers for at least 1 year, and a frequency of using digital services at least 3 times per month. This study used a questionnaire with a 5-point Likert scale. Quantitative data analysis was conducted through validity and reliability tests, classical assumption tests, and multiple linear regression analysis. Hypothesis testing used t-tests, F-tests, and coefficients of determination. The results showed that risk perception had a significant negative effect on customer trust, while data security and transparency had a significant positive effect. Simultaneously, the three independent variables significantly influence Generation Z customer trust, contributing 65.4% (R² = 0.654), while the remaining proportion is influenced by other determinants that are outside the scope of the model. Among the three variables, data security and transparency have a stronger contribution to increasing trust than risk perception. These findings imply that Islamic banks need to proactively reduce customer risk perception through effective risk mitigation communication, strengthen data security systems with the latest technologies such as biometrics and encryption, and increase transparency of product information, fees, and terms and conditions in a clear and easy-to-understand manner. This research contributes to addressing the theoretical gap by integrating the three variables into a single unified model, as well as offering practical implications for the development of Islamic banking digital services oriented towards the younger generation.